Low-Cost, Accurate, Effective Treatment of Hypertensive Cerebral Hemorrhage With Three-Dimensional Printing Technology - Li, Ke; Ding, Xiangqian; Wang, Qingbo; Fan, Gangxian; Guo, Wei; Li, Chenglong; Li, Meng; Li, Zefu (Frontiers in Neurology, 2021)
Background: Hypertensive intracerebral hemorrhage (HICH) is an acute, severe neurosurgical disease. Puncture drainage of the hematoma has gradually been accepted as a surgical treatment for HICH because of its minimally invasive nature. The precision of the puncture is extremely high because of particular physiological functions. This study was performed to explore the effect of a navigation mold created by three-dimensional printing (3DP) technology in the surgical treatment of HICH. Material and methods: We conducted a retrospective analysis of all consecutive patients with ICH treated with minimally invasive surgery using 3DP navigation or craniotomy to remove the hematoma through a small bone window at the Binzhou Medical University Hospital from June 2017 to March 2019. In total, 61 patients were treated with minimally invasive surgery using 3DP navigation (3DP group), and 67 patients were treated with craniotomy to remove the hematoma through a small bone window (craniotomy group). A comparative study of the two groups was conducted to assess the preoperative and postoperative conditions. Results: The duration of the surgery was significantly longer in the craniotomy group than in the 3DP group (3.27 ± 1.14 h vs. 1.52 ± 0.23 h). Postoperative complication rates were significantly lower in the 3DP group than in the craniotomy group (18.0 vs. 34.3%). Moreover, the rate of patients with a Glasgow Outcome Scale score ≥4 points was not statistically significantly different in the two groups. Conclusion: Minimally invasive surgery assisted by 3DP navigation to treat patients with HICH appears to be safe and effective. The 3DP technique may improve the individualization and accuracy of the surgery.